Effect of Harvesting Method and Calcium on Post Harvest Physiology of Tomato - Bhattarai, DR; Gautam, DM (Nepal Agriculture Research Journal, 2009)
An experiment was conducted in Institute of Agriculture and Animal Science, Rampur, Chitwanduring 2003 to find out the effect of harvesting method and calcium chloride treatment on postharvestphysiology of tomato. Tomato (Hybrid Gootya) fruits with stalk and without stalk wereharvested at breaker stage and dipped in distilled water and different concentrations of calciumchloride viz. 0.25%, 0.50%, 0.75% and 1% for fifteen minutes. Fruit were then air-dried andstored at ambient condition (24 ± 3°C and 70 ± 5 % RH). Among the tested treatments the leastcumulative physiological weight loss (12.14%) was exhibited by 1% calcium chloride. The shelflife of tomato fruits was significantly affected by harvesting method and calcium treatment.Tomato fruit harvested with stalk had higher shelf-life (15 days) as compared to those harvestedwithout stalk (12.93 days) irrespective to calcium chloride application. The maximum shelf lifewas noticed in 1% calcium chloride treated fruits (16.50 days) followed by 0.75% calciumchloride treated fruits (16.17 days).Key words: Calcium chloride; physiological weight loss; shell life; tomatoDOI: 10.3126/narj.v7i0.1864Nepal Agriculture Research Journal Vol.7 2006 pp.37-41